- #1
dock
[SOLVED] (Don Kihot) fighting windmils
people!
i'm tyred of oposing each and every one of you.why don't someone, for a change, start to cooperate with me. you know that the way phisicist understand simple differential math just ain't right.i have hard evidence on this that no one can deny.just egknowledge my claims as rightfull.you have a junk-physics only to lose.
HERE IS WHAT I SAY IS WRONG IN GENERAL:
when you define v as dx/dt where x=x(t) then you cannot say that v is variable. you have to accept that v is constant.
same as if you assume that t=const then t=dx/dv where x=x(v).
if x=const then tdv=-vdt.
if none is constant then dx=vdt+tdv or x=vt.
it's not only dx=vdt but for every law with the form x=vt you do the same.for example dE=Fdx
Newton's dynamics:
dE(potential)=-FdR=-(wmMdR)/R^2 <=> E=(wmM)/R
dE(kinetic)=Fdx=madx=mdV(dx/dt)=mVdV <=> E=mVV/2
here you are talking about any (F and V) and yet F=const, V=const
FULL STOP.
PS: don't be afraid of the changes cause they are good.
people!
i'm tyred of oposing each and every one of you.why don't someone, for a change, start to cooperate with me. you know that the way phisicist understand simple differential math just ain't right.i have hard evidence on this that no one can deny.just egknowledge my claims as rightfull.you have a junk-physics only to lose.
HERE IS WHAT I SAY IS WRONG IN GENERAL:
when you define v as dx/dt where x=x(t) then you cannot say that v is variable. you have to accept that v is constant.
same as if you assume that t=const then t=dx/dv where x=x(v).
if x=const then tdv=-vdt.
if none is constant then dx=vdt+tdv or x=vt.
it's not only dx=vdt but for every law with the form x=vt you do the same.for example dE=Fdx
Newton's dynamics:
dE(potential)=-FdR=-(wmMdR)/R^2 <=> E=(wmM)/R
dE(kinetic)=Fdx=madx=mdV(dx/dt)=mVdV <=> E=mVV/2
here you are talking about any (F and V) and yet F=const, V=const
FULL STOP.
PS: don't be afraid of the changes cause they are good.